Enhancing Fastness and Ultraviolet Protection Factor of Pelthophorum pterocarpum Natural Dye by Titania Nanoparticles Modification - Budiasih, K.S.; Kusumawardani, C.; Khoirunisa, I. (Asian Journal of Chemistry, 2023)
The harmful effects of synthetic dyes on the environment can be mitigated through the use of natural dyes in textiles. However, textile dyeing with natural dyes has low brightness and colour resistance. TiO2 nanoparticles modified copper pod (Pelthophorum pterocarpum) dye (TMCD) was studied to enhance the fastness and ultraviolet protection factor of fabrics dyeing. This study was conducted using a cotton fabrics which processed by some mordant agents. TiO2 in various amount were dispersed in aqueous copper pod bark solution and produced a modified copper pod natural dye. Investigation of the dyed fabrics was conducted in 3 parameters viz. the colour direction, fastness values toward sunlight and ultraviolet protection factor (UPF). The results showed that the mordant agents affect the final colour palette and brightness, suggesting that TiO2 improved the colour intensity and fastness value of copper pod dye. It also enhanced the ultraviolet protection factor (UPF) of dyed fabrics by 3-8 point higher than the control groups.